Charged isotropic solutions with linear barotropic equations of state in Einstein–Gauss–Bonnet gravity - Siyamthanda Remember Mngadi; Sudan Hansraj (European Physical Journal C: Particles and Fields)
Abstract In the present work we investigate new class of charged isotropic solutions with a linear barotropic equation of state (EoS) in the framework of Einstein–Gauss–Bonnet (EGB) gravity for 5 and 6 dimensional spherically symmetric static distributions. Imposing such a restriction of the EoS, one more further assumption on the metric potentials must be chosen in order to close the system. For example, the constant gravitational potential which is responsible for an isothermal distribution in Einstein gravity and as well as different forms of temporal potential are analyzed. Through graphical analysis we demonstrate that the obtained exact models satisfy the basic elementary astrophysical requirement for physical plausibility.